Energy coupling during the August 2011 magnetic storm. Issue 2 (11th February 2014) - Huang, C. Y.; Su, Y.‐J.; Sutton, E. K.; Weimer, D. R.; Davidson, R. L.
Abstract We present results from an analysis of high‐latitude ionosphere‐thermosphere (IT) coupling to the solar wind during a moderate magnetic storm which occurred on 5–6 August 2011. During the storm, a multipoint set of observations of the ionosphere and thermosphere was available. We make use of ionospheric measurements of electromagnetic and particle energy made by the Defense Meteorological Satellite Program and neutral densities measured by the Gravity Recovery and Climate Experiment satellite to infer (1) the energy budget and (2) timing of the energy transfer process during the storm. We conclude that the primary location for energy input to the IT system may be the extremely high latitude region. We suggest that the total energy available to the IT system is not completely captured either by observation or empirical models.